Reductive Etherification of Fatty Acids or Esters with Alcohols using Molecular Hydrogen. Issue 12 (23rd May 2016) - Erb, Benjamin; Risto, Eugen; Wendling, Timo; Gooßen, Lukas J.
Abstract: In the presence of a catalyst system consisting of a ruthenium/triphos complex and the Brønsted acid trifluoromethanesulfonimide, mixtures of fatty acids and aliphatic alcohols are converted into the corresponding ethers at 70 bar H2 . The protocol allows the sustainable one‐step synthesis of valuable long‐chain ether fragrances, lubricants, and surfactants from renewable sources. The reaction protocol is extended to various fatty acids and esters both in pure form and as mixtures, for example, tall oil acids or rapeseed methyl ester (RME). Even the mixed triglyceride rapeseed oil was converted in one step. Abstract : Into the ether : In the presence of a catalyst system consisting of a Ru/triphos complex and the Brønsted acid trifluoromethanesulfonimide, mixtures of fatty acids and aliphatic alcohols are converted into the corresponding ethers at 70 bar H2 . The protocol allows the sustainable one‐step synthesis of valuable long‐chain ether fragrances, lubricants, and surfactants from renewable sources.